(untitled) (Homoeopathy for All, 2025)
The human gastrointestinal system is far more than a digestive organ; it is an intricate neuro-biological network often referred to as the body’s “second brain.” This concept arises from the enteric nervous system (ENS), a vast collection of over 100 million neurons capable of independently regulating motility, secretion, and sensory perception without direct cortical input. Disturbances in this neuro-gastrointestinal axis are now recognized as central to the development of indigestion as acute course or functional dyspepsia (FD) in chronic course, a condition characterized by postprandial fullness, early satiety, epigastric discomfort, bloating, nausea, and impaired gastric accommodation.